Fatigue-Prone Details in Steel Bridges - Haghani, Reza; Al-Emrani, Mohammad; Heshmati, Mohsen (Buildings (Basel), 2012)
This paper reviews the results of a comprehensive investigation including more than 100 fatigue damage cases, reported for steel and composite bridges. The damage cases are categorized according to types of detail. The mechanisms behind fatigue damage in each category are identified and studied. It was found that more than 90% of all reported damage cases are of deformation-induced type and generated by some kind of unintentional or otherwise overlooked interaction between different load-carrying members or systems in the bridge. Poor detailing, with unstiffened gaps and abrupt changes in stiffness at the connections between different members were also found to contribute to fatigue cracking in many details.